Vitamin K Supplementation for Reducing Cardiovascular Events in End-Stage Chronic Kidney Disease: A Systematic Review - Liora, Kevin; Wiyono, Putri Dhiya Prameswari; Putra, Ananda; Alexander, Devin; Ramadhan, Afif; Oktavia, Anissya Rima; Larissa, Olivia; Nugroho, Fajar Prianto; Tjahyanto, Teddy (International Journal of Public Health Excellence (IJPHE), 2024)
This study was conducted to analyze the hSIL of Vitamin K Supplementation in Reducing Cardiovascular Events in End-Stage Chronic Kidney Disease: A Systematic Review. Cardiovascular disease (CVD) is the leading source of morbidity and mortality worldwide, and chronic kidney disease (CKD) is a major contributor to this matter. Kidney disease is estimated to affect over 850 million people worldwide. The present systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We searched studies from electronic databases (PubMed Central, ScienceDirect, PLoS One, Google Scholar, Nature). Studies were considered eligible if they met the following criteria : (1) the study is a randomized controlled trial (RCT), (2) the study was published in the last 5 years (2018– 2022), (3) the study participants were adult patients with kidney disease from stage III to end-stage who were given vitamin K supplementation, (4) the study reported coronary artery calcium scores pre- and post- vitamin K supplementation, (5) the study was published in English. Risk of bias of each study was evaluated using Cochrane Risk of Bias (RoB) 2 tool. Data were descriptively examined and narratively reported. In conclusion, our results do not suggest that vitamin K supplementation may affect vascular calcification as measured by the CAC score. Up till now there is no treatment to reverse vascular calcification in ESKD patients. The current clinical practice should focus on prevention and retardation of its progression.